2006
DOI: 10.1007/11731139_52
|View full text |Cite
|
Sign up to set email alerts
|

IMB3-Miner: Mining Induced/Embedded Subtrees by Constraining the Level of Embedding

Abstract: Tree mining has recently attracted a lot of interest in areas such as Bioinformatics, XML mining, Web mining, etc. We are mainly concerned with mining frequent induced and embedded subtrees. While more interesting patterns can be obtained when mining embedded subtrees, unfortunately mining such embedding relationships can be very costly. In this paper, we propose an efficient approach to tackle the complexity of mining embedded subtrees by utilizing a novel Embedding List representation, Tree Model Guided enum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 13 publications
0
72
0
1
Order By: Relevance
“…Một số tác giả sử dụng cơ sở dữ liệu cây weblogs CS-LOG [25,26,28]. Các thuật toán của các nhóm tác giả này đều có những điểm mạnh và điểm yếu vì vậy việc so sánh hiệu suất thực hiện chỉ mang tính chất tương đối.…”
Section: Giới Thiệuunclassified
“…Một số tác giả sử dụng cơ sở dữ liệu cây weblogs CS-LOG [25,26,28]. Các thuật toán của các nhóm tác giả này đều có những điểm mạnh và điểm yếu vì vậy việc so sánh hiệu suất thực hiện chỉ mang tính chất tương đối.…”
Section: Giới Thiệuunclassified
“…This enumeration is a bottom-up approach that generates non-redundant candidates [18]. A candidate generation technique can generate valid frequent and infrequent candidates as well as invalid frequent and infrequent candidates.…”
Section: Tree Structure Guided Scheme Based Enumerationmentioning
confidence: 99%
“…From fig 6(b), it can be observed that SLEUTH generated more frequent subtrees in comparison to BEST, as it uses the opportunistic pruning technique which does not fulfil the downward closure lemma and may generate pseudo frequent subtrees [18].…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…A task in data mining is characterized by the type of data, structures and patterns to be found [8,9]. Advancements in data collection technologies have contributed to the high volumes of sales data.…”
Section: Introductionmentioning
confidence: 99%
“…One way to achieve efficient processing is to develop an intermediate memory construct that helps us to easily process and manipulate something. We showed this in [9] by developing an efficient intermediate memory construct called Embedding List (EL) [9,10] to efficiently mine frequent embedded subtrees. The problem of using such intermediate memory constructs is that it demands some additional memory storage.…”
Section: Introductionmentioning
confidence: 99%